The interfaces of language in use: a functionalist treatment of the entity clause - Neves, Maria Helena de Moura [UNESP] (Federal Univ Ceara, 2023)
The aim of the study is, based on the functionalist theory of language, to problematize the interfaces of the language in use, placing special focus on the grammar that governs language and considering the entire environment of language production. In search of parallels with the text itself, the starting point is the entity clause, which is problematized as organization of information, as organization of linguistic interaction and as semantic organization. Comes into question the processing of the configuration of the linguistic chains which are produced, considered the interface with the making of language, expanded in the living of the language community. In the examination it is evident that, for the semantic result and for the intended pragmatic effect, the existence of a pragmatic determination on the syntactic arrangement is relevant. The conclusion is that the awareness of this integration that triggers grammar, leading to linguistic production, is what allows the analytical separation of processes, guaranteeing theoretically sustained analyses.
Keywords: clause; text; pragmatic determination; syntactic arrangement; semantic result